“Not a Chinaman’s Chance”: Chinese labour in South Africa and the United States of America (Historia, 2021)
EnglishChinese labour formed an integral part of the mass migration of people in the international era of industrial capitalism. The developing economies of colonial mining, plantation and railway developments, precipitated these movements. The Chinese labour force, which was stereotyped as hard-working, diligent and reliable, was as much welcomed as it was later objected to. As a subaltern class of contracted or indentured people, they were completely lacking in power, their voices were not readily recorded and were therefore not heard. The anti-Chinese campaigns which resonated across the Atlantic and the Pacific Oceans reveal remarkable similarities in terms of anti-Sinicism and Orientalism. This article attempts to juxtapose these situations by comparing and contrasting the place and position of these labourers in terms of the attitudes and actions of the colonial employer, as well as the visual representations of the “other”. This eventually culminated in some of the first overtly racist legislation introduced during the genesis of white hegemony in the various colonial destinations, namely the Chinese Exclusion Acts.     Afrikaans“Not a Chinaman’s Chance”: Sjinese arbeid in Suid-Afrika en die Verenigde State van Amerika Sjinese arbeid het ŉ integrale deel van die grootskaalse migrasie van mense tydens die internasionale era van industriële kapitalisme uitgemaak. Die ontwikkelende ekonomieë van koloniale mynbou, plantasie- en spoorwegontwikkeling, het hierdie verhuising aangevuur. Die Sjinese arbeidsmag, wat gestereotipeer is as hardwerkend, ywerig en betroubaar, is net soseer verwelkom, as wat dit later afgekeur is. As ŉ ondergeskikte klas bestaande uit gekontrakteerde of ingeboekte mense, het hulle oor geen mag beskik nie. Hulle stemme is nie geredelik aangeteken nie en is daarom ook nie gehoor nie. Die anti-Sjinese veldtogte wat oor die Atlantiese en Stille Oseane weerklink het, vertoon merkwaardige ooreenkomste wat anti-Sinisisme en -Oriëntalisme betref. Hierdie artikel poog om dié gevalle naas mekaar te stel deur die plek en posisie van hierdie arbeiders in terme van die houding en optrede van hulle koloniale werkgewers, asook die visuele uitbeelding van hulle as “die ander”, met mekaar te vergelyk en te kontrasteer. Dit het uiteindelik gelei tot van die eerste openlik rassistiese wetgewing wat tydens die ontstaansjare van wit hegemonie in die onderskeie koloniale gebiede aanvaar is, naamlik die “Chinese Exclusion Acts”.
Keywords: Anti-Chinese; Chinese Exclusion Act; Chinese labour; comparative history; orientalism; South Africa; United States of America; Anti-Sjinees; Oriëntalisme; Sjinese arbeid; Suid-Afrika; Verenigde State van Amerika; vergelykende geskiedenis